Human Preference and Fractal Dimension - Pihel, Johan (2011)

(untitled)
The objective of this study is to assess any connections between the fractal dimension of edges in images of pastoral landscapes in Sweden and preference rating of the images and preference ratings for the edge images respectively. 23 participants volunteered for the trial. The mean age was 29,95 years, six of the subjects where women. The study consited of analysis of fractal dimension in images of pastoral landscapes from an earlier study and an experiment with human participants. The subjects estimated their preference for manipulated images, edge images, of pastoral landscapes. Their results where compared to results from the earlier study on non manipulated images. The result show that significant connection exists and in a way that correlates well with earlier studies. The edge images did not have significant correlation. Results for the edge images: (rs = 0.015, p<0.0001), and the original images: (rs = -0.853, p<0.0001). Furthermore the study discuss the concept “preference” and however that concept needs to be more defined if it is to be useful. 2